Sisuko: The Efforts to Digitize Financial Management of Suko-Suko Canal Tourism in Sukorejo Village, Jember Regency - Aprillianto, Bayu; Budi Sulistiyo, Agung; Wulandari Widiyanti, Novi; Ayu Wulandari, Gusti; Agustriono, Aldi; Indah Purnamawati; Rafly Syah Maulidy (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Sukorejo Village is a village that has natural potential for river beauty and local wisdom in the Bangsalsari District area, Jember Regency. In 2024, Sukorejo Village will succeed in having its first tourist destination called Suko-Suko Canal Tourism. In the sustainability efforts of the service team, which aims to form a sustainable financial management system for tourism by adopting digital technology through the preparation of a digital financial report preparation application called SiSuko, continued with activities to increase the human resource capacity of village officials, tourism managers, and MSMEs in financial literacy and digital-based financial management and the use of applications SiSuko. The results of the activity show that the public is enthusiastic and actively participates in the process of preparing financial report applications SiSuko so that the resulting application is user-friendly and meets the needs of the target audience. Meanwhile, activities to increase human resource capacity showed positive results with increased financial literacy and digital financial management and targets being able to use applications SiSuko.